636. The Hepcidin-25 and Iron Kinetics During the Acute Phase of Systemic Infection. (26th November 2018) - Moro, Hiroshi; Bamba, Yuuki; Nagano, Kei; Koizumi, Takeshi; Aoki, Nobumasa; Ohshima, Yasuyoshi; Watanabe, Satoshi; Koya, Toshiyuki; Takada, Toshinori; Kikuchi, Toshiaki
Abstract: Background: Hepcidin-25, a central regulator of iron metabolism, can decrease serum iron levels by inhibiting the iron transporter ferroportin. Production of hepcidin-25 in hepatocytes is tightly regulated by various stimulations and is promoted by inflammation via the IL-6 pathway. The role of hepcidin-25 in acute infections has not been fully understood; therefore, we investigated the hepcidin and iron kinetics during the acute phase of systemic infection. Methods: We collected clinical samples of bloodstream infections at various stages and measured plasma hepcidin-25 levels using surface enhanced laser desorption/ionization time-of-flight mass spectrometry. In addition, plasma levels of IL-6, C-reactive protein, procalcitonin, presepsin, lipocalin-2 were measured. Results: In this study, 50 patients (median age: 72 years; 52% males) were included. In the acute phase of infection (first 3 days after onset of symptom), plasma hepcidin-25 levels were rapidly elevated, accompanied with a reduction in serum iron concentration. As the inflammation subsequently resolved and the patients' general condition improved (≥10 days after symptom onset), serum hepcidin-25 levels were decreased and serum iron levels were restored. Therefore, hepcidin-25 and iron levels dynamically vary during the acute phase of infection, and the enhanced production of hepcidin-25 due to severe inflammation can precipitate a rapid decrease of serum iron levels. This series of reactions may be regarded as a host defense involving the inhibition of the nutrient acquirement of bacteria. In this setting, the iron requirement of bacteria is expected to be increased and the iron uptake of bacteria via iron transporter systems may be activated. Conclusion: During the acute phase of infectious disease with severe inflammation, iron levels were immediately decreased due to enhanced production of hepcidin-25. Understanding of host iron status may be essential for effective use of siderophore cephalosporin, with a unique mechanism of action involving the use of bacterial iron uptake systems. Disclosures: All authors: No reported disclosures.